If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3y + -17 Reorder the terms: 7 = -17 + 3y Solving 7 = -17 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 7 + -3y = -17 + 3y + -3y Combine like terms: 3y + -3y = 0 7 + -3y = -17 + 0 7 + -3y = -17 Add '-7' to each side of the equation. 7 + -7 + -3y = -17 + -7 Combine like terms: 7 + -7 = 0 0 + -3y = -17 + -7 -3y = -17 + -7 Combine like terms: -17 + -7 = -24 -3y = -24 Divide each side by '-3'. y = 8 Simplifying y = 8
| 6x-(4x-32)=0 | | 125m-100m+43,650=45,675-300m | | (16x-3)(4)=0x | | 4(6p-3)=-39-3p | | -.4*p+2=.2*p+11 | | (16x-3)(4)=0 | | 10x-6=7x | | y+(-10)=36 | | 8y+1=2y-26 | | .5f+10=48 | | 6(2x+3)+2= | | (16x-3)(2)=0 | | 8p+9p=34 | | a-6-7a=1-6a | | 11c-4-3=8 | | (16x-3)(8)=0 | | 1/3x-1/6y=1 | | -4/5a=12/17 | | 2x-6=8-2x | | 3=2y | | 16x+3=47 | | 4+17/-2=0 | | 8(2a-8)=-4(-3a+6) | | 2c+c+12=14 | | 1/2f+10=48 | | 33/d=12 | | z/14=-28 | | 1-2x=-9+8x | | 8x+4x+2=12x+2 | | 87=(2x+7) | | x^2+3x+14=47.75 | | (15)t+(9)=15t+9 |